Heidi - Spyri, Johanna; Howell, Troy (Wanderer Books, 1982)
An orphan sent to live with her grandfather learns to love both the old man and the Swiss Alps and is homesick when she goes to the city to be a companion to an invalid.
Reprint. Originally published: New York : Grosset & Dunlap, 1945.(Illustrated junior library)
Translation of: Heidi.
An orphan sent to live with her grandfather learns to love both the old man and the Swiss Alps and is homesick when she goes to the city to be a companion to an invalid.
Keywords: Orphans / Juvenile fiction. / http://id.loc.gov/authorities/subjects/sh2008108587; Grandfathers / Juvenile fiction. / http://id.loc.gov/authorities/subjects/sh2008105028; Mountain life / Juvenile fiction. / http://id.loc.gov/authorities/subjects/sh2008107235; Switzerland / Juvenile fiction. / http://id.loc.gov/authorities/subjects/sh2008111544